Correlation of visual recovery time after laser refractive surgery with preoperative keratometry and astigmatism among myopic astigmatism patients - Akhtar Ali, Ahmad Nurfahmi; Md Mustafa, Md Muziman Syah; Rahim, Fadzilah Hanim; Ahmad Fauzi, Nadhirah; Mohd. Kamal, Khairidzan; Hilmi, Mohd Radzi (2020)
Introduction: Photorefractive keratometry (PRK) and laser in situ keratomileusis (LASIK) are among the many types of laser refractive surgery available for the correction of myopic astigmatism. The outcome of the procedure can be affected by several parameters which include patient’s age, optical zone diameter, epithelial hyperplasia, preoperative keratometry as well as astigmatism. Aim: This study aimed to determine the relationship between preoperative keratometry and astigmatism with visual recovery time after laser refractive surgery. Methods: Records of 174 eyes (174 patients) with myopic astigmatism who had been treated with either LASIK (71 eyes) or PRK (103 eyes) at IIUM Eye Specialist Clinic from January 2015 to June 2018, were retrospectively analyzed. Main outcome measure was the time taken for patients to achieve visual acuity (VA) 6/6 (equivalent to 0.00 LogMAR) postoperatively. Value for keratometry parameter was taken from corneal topography while astigmatism magnitude was taken from manifest refraction. Their correlation with visual recovery time was analyzed using Pearson correlation coefficient (PCC). P <0.05 was considered as statistically significant. Results: The mean preoperative astigmatism and mean keratometry was 0.9 ±0.76D and 43.65 ±1.23D respectively. A significant but weak positive correlation between preoperative astigmatism and visual recovery time was observed (P-value = 0.013; R = 0.188), while no correlation observed for mean keratometry (P-value = 0.305; R = 0.078). Conclusions: Preoperative astigmatism influenced the visual recovery time post laser refractive surgery in myopic astigmatism patients, but not keratometry.